Vitamin E Acetate Determination in Vaping Liquids and Non-targeted Analysis of Vaping Emissions of Diluents of Concern, Vitamin E Acetate and Medium-Chain Triglycerides Oil - Kosarac, Ivana; Kubwabo, Cariton; Katuri, Guru Prasad; Petraccone, Dora; Mischki, Trevor K. (Frontiers in Chemistry, 2021)
During the summer of 2019, cases of lung injury associated with vaping emerged in North America, including among individuals who reported exclusive use of nicotine vaping liquids. Once vitamin E acetate was identified as a potential causative agent a quantitative method based on a simple sample dilution, separation by gas chromatography and analysis by triple quadrupole mass spectrometry (GC MSMS) was developed. Method detection limit (MDL) and limit of quantification (LOQ) were determined at 0.159 µg/mL and 0.505 µg/mL, respectively. The analysis was performed on a subset of 203 commercially sourced nicotine containing vaping liquids of various flavour profile and nicotine range (nicotine free-59 mg/mL) from an internal inventory. The target analyte, Vitamin E Acetate, was not detected in any samples analyzed, as expected, given the reported detection in literature and high association of the chemical with cannabis and not nicotine containing vaping products. Emissions profiles of vitamin E acetate and Medium Chain Triglycerides (MCT) oil were also characterized via non-targeted analysis, using GC-MS/MS, to identify potential chemical analytes generated when liquids were heated. The emissions were generated under standardized conditions using a vaping machine and a vaporizer device designed for use with cannabis concentrates. Vitamin E acetate emissions mainly contained target analyte itself, while MCT oil emissions were more chemically complex, as expected due to the presence of various triglycerides in the un-vaped oil. Of note even following rigorous cleaning procedures of the device and contact parts with a number of chemical solvents and replacement of consumable parts between MCT oil and vitamin E acetate vaping sessions, cross-contamination was observed. This cross contamination and residue persistence, is indicative of a real-life scenario where users may share or use the same device with a number of different products or formulations and not be aware of potential exposures to diluents of concern.